Pengaruh Motivasi Belajar dan Gender Terhadap Prestasi Belajar IPA Siswa Kelas Bilingual SMP (SLUB) Saraswati 1 Denpasar - Gusti Ayu Dewi Setiawati; Anak Agung Putu Arsana (Universitas Sebelas Maret, 2018)
The purposes of this study are; (1) to prove whether there is a positive and significant effect of learning motivation on the science learning achievement of bilingual class student SMP (SLUB) Saraswati 1 Denpasar, (2) to prove whether there is positive and significant gender effect on the science learning achievement of bilingual class student SMP (SLUB) Saraswati 1 Denpasar, and (3) to prove whether there is a positive and significant effect of learning motivation and gender together on science learning achievement of bilingual class student SMP (SLUB) Saraswati 1 Denpasar. This is an ex post facto research. The population were all bilingual class students of SMP (SLUB) Saraswati 1 Denpasar. The sample was determined by saturated sampling technique. The data were obtained by questionnaire instrument of learning motivation, documentation of student's personal data and student's learning achievement score from their teachers. Instruments tested by the validity of Product Moment Pearson, internal validity of expert judgement, and reliability with Alpha Cronbach Test. Data of learning motivation, gender and science learning achievement in this research were analyzed by multiple linear regression analysis with SPSS 19 for Windows software. The results of this study are as follows. (1) There is no significant effect (p> 0,05) learning motivation on science learning achievement of bilingual class student SMP (SLUB) Saraswati 1 Denpasar. (2) There is no significant (p> 0,05) gender effect on science learning achievement of bilingual class student SMP (SLUB) Saraswati 1 Denpasar. (3) There is no significant effect (p> 0,05) learning motivation and gender simultaneously on the science learning achievement of bilingual class student SMP (SLUB) Saraswati 1 Denpasar.